A new era for medical liability in Italy: back to positivism - Armocida, Emanuele (Acta Biomedica Atenei Parmensis, 2020)
In 2017, the italian Chamber of Deputies approved the law n. 24 of 2017 (so-called “Gelli”) on professional liability of healthcare professionals. One of the most significant innovations contained in the "Gelli" Law is a new provision in case of medical malpractice (‘imperizia’), where the healthcare professional will avoid liability if he or she can show that they have acted in accordance with recommended guidelines published under law. In the absence of these guidelines the professional must adhere to principles of good practice.1 Guidelines  provided by the law aim to standardize medical acts. They are based on the principles of evidence-based medicine, an approach to medical practice aimed at optimizing the decision-making process. In literature many physicians and jurists have commented, in a discordant manner, the choices of the Legislator. In this article a historical perspective is proposed, finding analogies between the principles of the "Gelli" law and positivist thought. The evolution that Positivism has had in the medical field has been analyzed, in particular studying the evolution of the thought of the Italian physician and strong positivist Paolo Mantegazza (1831-1910).In light of the facts it is concluded that the physician must always keep in mind that medicine is a science applied to man, and any medical act must be a consequence of a doctor-patient concordance that inevitably takes into consideration every single individual in his uniqueness. Thus, although difficult the next step of the legislator should be to favor the establishment of high-quality medical-patient relationships. In any case, if the physician has been most careful in managing a good relationship with each individual patient and in understanding her/his situation before performing medical acts, she/he may perhaps fear less potential judicial repercussions.